Physicochemical and microbiota characterization of Paya Nie Ecotourism Reservoir for optimizing sustainable fisheries cultivation - Dani Pratama Putra; Azhar, Rossy; Izwar, Akmal; Setianingsih, Putri Ayu (Acta Aquatica: Aquatic Sciences Journal, 2025)
This study aims to analyze the physicochemical characteristics and microbiota communities in the Paya Nie Ecotourism Reservoir as a basis for water quality management for sustainable fisheries cultivation. Sampling was conducted at ten points representing the western, central, and eastern parts of the reservoir. Parameters measured included temperature, clarity, turbidity, pH, salinity, dissolved oxygen (DO), ammonia, phosphate, nitrate, COD, BOD, plankton density, and Escherichia coli. The results showed that most parameters were still in accordance with quality standards (PP No. 22 of 2021), especially pH (7.03–7.97), ammonia (0.001–0.028 mg/L), phosphate (2.6–3.9 mg/L), and nitrate (0.02–2.0 mg/L). However, DO levels at several stations were low (1.67–3.33 mg/L), while COD (500–926 mg/L) and BOD (1.00–2.47 mg/L) exceeded the threshold, indicating a high organic pollution load. The highest E. coli value was recorded at Station X (744.33 CFU/100 ml), indicating contamination from domestic activities. The dominant plankton species were Euglena sp. and Eudorina sp., indicating the waters are classified as productive but potentially eutrophic. The results of this study emphasize the need for waste management, cage density regulation, and routine water quality monitoring to maintain ecosystem balance and support the sustainability of fish farming in the Paya Nie Reservoir. Keywords: Microbiota; Paya Nie Reservoir; Physicochemistry; Sustainable Fisheries; Water Quality